The Quality, Quantity and Age of Giving Breastfeeding for Toddlers in Relation with Nutritional Status (Public Health Perspective Journal, 2019)
Malnutrition is one of the main causes of malnutrition. Globally, poor nutritional status is one of the causes of under-five mortality. The purpose of this study was to analyze the effect of the quality, quantity and age of providing complementary food for breast milk in relation to the nutritional status of children.This study was an observational study with a cross sectional study design. The population of toddlers aged 7-24 months is 344 toddlers, a sample of 77 toddlers. Data retrieval is using simple random sampling technique using Slovin formula.The results are showed that the three independent variables affected the nutritional status of children. The obtained is p-value (0.001) quality, (0,000) quantity and age (0,000).Based on the results of the study, it can be concluded that there is a relationship between the quality of complementary food for breast milk to the nutritional status of children with ap value of 0.001 (p 0.05), there is a relationship between the quantity of complementary food for the nutritional status of children with p value amounting to 0,000, and there is a relationship between the age of providing complementary food for breast milk to the nutritional status of children with ap value of 0.000. This research is expected to benefit the community. For information on the program of dissemination and counseling on the quality and quantity of complementary feeding for mother's milk the which is good in the family and the impact the caused by nutritional problems in infants.Â